(untitled) (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
This article analyzes the impact of climate change on gross domestic product (GDP) and economic growth processes in Uzbekistan based on theoretical and empirical approaches. The study examines the mechanisms through which drought, rising temperatures, decreasing water resources, and extreme weather events affect economic activity within the context of global climate change. In addition, the dynamics of pollutants released into the atmosphere across the regions of Uzbekistan during 2020–2024 are assessed using data from the National Statistics Committee (Stat.uz), and the most problematic regions are identified. The article explains the adverse effects of climate factors on economic growth by drawing on the empirical findings of researchers such as Melissa Dell, Benjamin F. Jones and Benjamin A. Olken, as well as Marshall Burke, Solomon Hsiang, and Edward Miguel. The study concludes by developing normative-legal and institutional recommendations aimed at strengthening the transition to a green economy, improving energy efficiency, reducing emission intensity per unit of GDP, promoting electric vehicles, enhancing digital monitoring, and reinforcing adaptation policies in the Aral Sea Basin.